2020
DOI: 10.1186/s13000-020-01008-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-541 serves as a prognostic biomarker of osteosarcoma and its regulatory effect on tumor cell proliferation, migration and invasion by targeting TGIF2

Abstract: Background: Several studies reported the dysregulation of miR-541 in the progression of some human malignancies. Osteosarcoma (OS) is one of the most common primary malignant bone tumors. This study aimed to assess the expression and clinical significance of miR-541 in OS patients and explore the biological function of miR-541 in tumor progression. Methods: Expression of miR-541 was detected by quantitative real-time PCR, and its prognostic value was evaluated using Kaplan-Meier survival analysis. The biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Ji et al illustrated that miR-421 promotes cell invasion and proliferation in HNSCC cell lines [32], which is in accordance with our results. Studies have shown that miR-541 inhibits the proliferation, migration, and invasion of osteosarcoma cells and that miR-622 downregulation is significantly associated with poor prognosis in various other tumors; these are contrary to our predicted miRNA functions in HNSCC [33][34][35]. However, there have been few studies on their functions in HNSCC.…”
Section: Discussioncontrasting
confidence: 99%
“…Ji et al illustrated that miR-421 promotes cell invasion and proliferation in HNSCC cell lines [32], which is in accordance with our results. Studies have shown that miR-541 inhibits the proliferation, migration, and invasion of osteosarcoma cells and that miR-622 downregulation is significantly associated with poor prognosis in various other tumors; these are contrary to our predicted miRNA functions in HNSCC [33][34][35]. However, there have been few studies on their functions in HNSCC.…”
Section: Discussioncontrasting
confidence: 99%
“…MiR-541 was reported that the dysregulation of the miR-541- ATG2A/RAB1B axis plays a key role in determining the patient’s response to sorafenib treatment [ 8 ]. Moreover, miR-541 could inhibit proliferation and migration in osteosarcoma cells and prostate cancer (PCa) cells [ 9 , 10 ]. Although miR-541-5p research is of great significance, its role in the RIPF research mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a transcription regulator, TGF-β-induced factor homeobox 2 (TGIF2) has been verified to be linked to the regulation of development and progression in various cancers. 21,22 In terms of lung cancer, it has been reported that TGIF2 promotes the progression of lung adenocarcinoma by regulating EGFR/RAS/ERK signaling. 23 Also, the upregulation of TGIF2 could aggravate the malignancy of tumors in NSCLC cells by boosting proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%